Ozone effect on inflammatory and proteomic profile of human macrophages and airway epithelial cells. (30th September 2020) - Falcone, L; Aruffo, E; Di Carlo, P; Del Boccio, P; Cufaro, M C; Pesce, M; Patruno, A; Ballerini, P
Abstract: Background: Reactive oxygen species (ROS) and oxidative stress in the respiratory system are involved in lung inflammation and tumorigenesis. Ozone (O3) is one of the main components of air pollution in urban areas able to act as strong pro-oxidant agent, however its effects on human health is still poorly investigated. In this study the effect of O3 has been evaluated in THP-1 monocytes differentiated into macrophages with PMA and in HBEpC (primary human bronchial epithelial) cells, two model systems for in vitro studies and translational research. Methods: Cell viability, ROS and pro-inflammatory cytokines like interleukin-8(IL-8) and tumor necrosis factor(TNF-α) have been tested in the above-mentioned cell lines not exposed to any kind of pollution (basal condition-b.c.) or exposed to O3 at a concentration of 120 ppb. In HBEpC a labelfree shotgun proteomics analysis has been also performed in the same conditions. Results: Ozone significantly increased the production of IL-8 and TNF-α in THP-1 whereas no changes were shown in HBEpC. In both cell lines lipopolysaccharide(LPS) caused an increase of IL-8 and TNF-α production in b.c. and O3 treatment potentiated this effect. Ozone exposure increased ROS formation in a time dependent manner in both cell lines and in THP-1 cells a decrease in catalase activity was also shown. Finally, according to these data, functional proteomics analysis revealed that in HBEpC exposure to O3 many differential proteins are related to oxidative stress and inflammation. Conclusions: Our results indicate that O3, at levels that can be reached in urban areas, causes an increase of pro-inflammatory agents either per se or potentiating the effect of immune response stimulators in cell models of human macrophages and human airway epithelial cells. Interestingly, the proteomic analysis showed that besides the dysregulated proteins, O3 induced the expression of AKR1D1 and AKR1B10, proteins recognized to play a significant role in cancer development. Key messages: This study adds new pieces of information on the association between O3 exposure and detrimental effects on respiratory system. This study suggests the need for further research on the mechanisms involved and for a continued monitoring/re-evaluation of air pollution standards aimed at safeguarding human health.